The peculiarities of student’s moral norms - ZAJANČKAUSKAITĖ, LORETA (Psichologija, 1997)
Moral norms are reflections of society’s general interests. Very often those general interests are contrary to individual interests. For this reason,the scientific research of moral phenomenon bas much value. The article deals with moral knowledge and readiness for the violation of any declared norms. In the course of socialisation, individuals meet the same values and norms of behavior, but the results show statistically meaningful intergroup differences which are displayed by the declared norms’ contents, a formulations of these norms, and a readiness for the violation of them. The groups researched were divided according to sex and age.